The attic : a memoir - Harnack, Curtis, 1927-2013 (University of Iowa Press, 2011)
In The Attic, his sequel to the classic We Have All Gone Away, Curtis Harnack returns to his rural Iowa homeplace to sift through an attic full of the trash and treasures left behind by the thirteen children in two generations who grew up in the big farmhouse. ℗¡℗¡℗¡℗¡℗¡ The adult Harnack had been making pilgrimages to his past from various parts of the country for thirty-plus years; now the death of an uncle and the disposal of an estate bring him home once more. The resonant diaries, church bulletins, photos, newspaper clippings, and other memorabilia in the attic allow him to rediscover both per.